When natural enemies go to sleep: diapause induction and termination in the pear psyllid predator Pilophorus gallicus (Hemiptera: Miridae). Issue 12 (15th May 2019) - Ramírez‐Soria, Maria J; Wäckers, Felix; Sanchez, Juan A
Abstract : Pilophorus gallicus can establish resident populations in orchards by entering diapause in winter. We studied diapause induction and termination to predict seasonal activity and improve its management in IPM programs. Abstract: BACKGROUND: Pilophorus gallicus Remane (Hemiptera: Miridae) is an important predator of the pear psyllid Cacopsylla pyri L. (Hemiptera: Psyllidae) in pear orchards ( Pyrus communis L. ‐Rosaceae‐). In the Mediterranean area, it has a multivoltine lifecycle, and can establish resident populations by entering into a facultative embryonic diapause to survive the winter season. Facultative diapause is regulated by environmental factors, and its role in population dynamics is essential because it determines the presence of active individuals in the field. The objective of this work was to investigate the effect of (i) photoperiod and temperature on diapause induction in P. gallicus and (ii) photoperiod, temperature, and exposure time on diapause termination. RESULTS: Diapause induction was triggered by a short photoperiod (9L:15D), whereas temperature did not influence it significantly. In contrast, diapause termination required a prolonged exposure to low temperature while photoperiod did not have a significant effect. At 6 °C, diapause termination increased significantly between 50 and 70 days of exposure, but not among 70, 90 and 150 days. The longer the exposure of diapausing eggs to 6 °C the shorter their hatching times. Additionally, three different reproductive classes were observed among the female population: diapause inducing, non‐diapause inducing, and mixed. CONCLUSION: This work contributes to the knowledge of the reproductive and overwintering strategy of P. gallicus . Embryonic diapause may greatly determine the structure of populations according to environmental conditions and the response of the predator as biological pest control agent. In addition, knowledge of the factors regulating egg diapause may be a useful tool for the mass rearing industry. © 2019 Society of Chemical Industry